Development and validation of the patient-reported traditional Chinese medicine kidney deficiency pattern scale for patients with colorectal cancer - Yunzi Yan; Yufei Yang; Chunhui Ning; Shaohua Yan; Lingyun Sun (Journal of Traditional Chinese Medical Sciences)
Objective: To develop a patient-reported traditional Chinese medicine kidney deficiency pattern (TCM-KDP) scale for colorectal cancer (CRC) patients and evaluate its reliability and validity. Methods: We administered the TCM-KDP questionnaire to postoperative patients with stage II and III CRC as part of a multicenter randomized controlled trial (RCT) conducted in China from December 2018 to September 2021. The TCM-KDP scale consists of eight items on patient-reported symptoms and is scored on a five-point Likert scale. The scale’s reliability was assessed using Cronbach’s α and test-retest reliability, while content validity was evaluated with the content validity index. We compared the differences in serum cytokine levels and other clinical factors between patients with higher and lower KDP scores. Results: Of the 378 patients analyzed in the original RCT, 352 (93.2%) completed the TCM-KDP questionnaire. The Cronbach’s α of the eight-item TCM-KDP scale was 0.734, and the test-retest reliability was 0.745. Our exploratory factor analysis yielded eight factors that explained the variance of 50.34%. The mean TCM-KDP score was 2.80 ± 0.92. Compared with patients with stage II CRC, those with stage III CRC had significantly higher TCM-KDP scores (2.25 vs. 2.50, P = .026). We categorized all patients into high- or low-KDP score groups (the cut-off score was 2.8). Patients with lower TCM-KDP scores had significantly higher serum interleukin-1β expression levels (P = .04). Conclusion: The patient-reported TCM-KDP scale demonstrated relatively good feasibility, internal consistency, and test-retest reliability among patients with CRC. Future studies could apply this scale to other cancer types and diseases.